Literature, theology and feminism - Walton, Heather (Book collections on Project MUSE., 2019)
'This book offers an authoritative overview of the broad and complex terrain of feminist theorising concerning the relationship between literature and theology as it has developed over the past several decades. It provides the first comprehensive evaluation of the significance of women's literature in the development of feminist theology and offers a critique of the variety of reading practices currently employed by religious feminists. As well as illuminating current reading strategies the work argues that it is now appropriate for feminists to develop new ways of reading the divine in women's writing. Drawing upon the pioneering work of Helene Cixous, Julia Kristeva and Luce Irigaray the work sets out a new framework for feminist religious reading that is both creative and challenging and which will be of interest both to scholars and students in this area.Through its artful and compelling feminist reconsiderations, the book makes a refreshing and significant contribution to the general field known as literature and theology' --Back cover.